Odpowiedzi

2010-02-04T19:50:35+01:00
-3x-2x=-10
-5x=-10/-5
x=2
b) 2x - 2 = 7 - x
2x+x=7+2
3x=9/3
x=3
c) 10 = 4 - 2x
2x=4-10
2x=-6/2
x=-3
d) -(2x - 1) = 4
-2x+1=4
-2x=4-1
-2x=3/-2
x=-3/2
e) 2(x+1) = x
2x+2=x
2x-x=-2
x=-2
f) 2t - (3t + 1) = 6
2t-3t-1=6
-t=6+1
-t=7/:(-1)
t=-7
g) - (4 + x) = 2(3-x)
-4x-x=6-2x
-5x+2x=6
-3x=6/(-3)
x=-2
h) 3(y + 6) - y = 2(y + 9)
3y+18-y=2y+18
2y-yy=18-18
0=0
i) (x-7) - 2 (3x + 5) = 3
x-7-6x-10=3
-5x=3+10+7
-5x=20/(-5)
x=-4







1 5 1
Najlepsza Odpowiedź!
2010-02-04T19:59:31+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=-10
-x=-2
x=2

b)2x-2=7-x
2x+x=7+2
3x=9
x=3

c)10=4-2x
2x=-10+4
2x=-6
x-=-3

d)-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3
-x=1,5
x=-1,5

e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f)2t-(3t+1)=6
-1t+2t-1=6
t=6+1
t=7

g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=4+6
x=10

h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y-2y=-18+18
0=0

i)(x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=7+10+3
-5x=20
-x=4
x=-4
4 3 4
2010-02-04T23:49:58+01:00
A)
-3x = 2x - 10
-3x-2x=-10
-5x=-10
x=2

b)
2x - 2 = 7 - x
2x+x=7+2
3x=9
x=3

c)
10 = 4 - 2x
2x=4-10
2x=-6
x=-3

d)
-(2x - 1) = 4
-2x+2=4
-2x=4-2
-2x=2
x=-1

e)
2(x+1) = x
2x+2=x
2x-x=-2
x=-2

f)
2t - (3t + 1) = 6
2t-3t-1=6
-t=6+1
-t=7
t=-7

g)
- (4 + x) = 2(3-x)
-4x-x=6-2x
-4x-x+2x=6
-3x=6
x=-2

h)
3(y + 6) - y = 2(y + 9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

i)
(x-7) - 2 (3x + 5) = 3
x-7-6x-10=3
-5x=3+7+10
-5x=20
x=-4